AcT-2: A Novel Myotropic and Antimicrobial Type 2 Tryptophyllin from the Skin Secretion of the Central American Red-Eyed Leaf Frog, Agalychnis callidryas - Lilin Ge; Peng Lyu; Mei Zhou; Huiling Zhang; Yuantai Wan; Bin Li; Renjie Li; Lei Wang; Tianbao Chen; Chris Shaw (The Scientific World Journal)
Tryptophyllins are a diverse family of amphibian peptides originally found in extracts of phyllomedusine frog skin by chemical means. Their biological activities remain obscure. Here we describe the isolation and preliminary pharmacological characterization of a novel type 2 tryptophyllin, named AcT-2, from the skin secretion of the red-eyed leaf frog, Agalychnis callidryas. The peptide was initially identified during smooth muscle pharmacological screening of skin secretion HPLC fractions and the unique primary structure—GMRPPWF-NH2—was established by both Edman degradation and electrospray MS/MS fragmentation sequencing. A. cDNA encoding the biosynthetic precursor of AcT-2 was successfully cloned from a skin secretion-derived cDNA library by means of RACE PCR and this contained an open-reading frame consisting of 62 amino acid residues with a single AcT-2 encoding sequence located towards the C-terminus. A synthetic replicate of AcT-2 was found to relax arterial smooth muscle (EC50 = 5.1 nM) and to contract rat urinary bladder smooth muscle (EC50 = 9.3 μM). The peptide could also inhibit the growth of the microorganisms, Staphylococcus aureus, (MIC = 256 mg/L) Escherichia coli (MIC = 512 mg/L), and Candida albicans (128 mg/L). AcT-2 is thus the first amphibian skin tryptophyllin found to possess both myotropic and antimicrobial activities.